Tahlil Bahts al Naqd al Adabi al Nisawiy min Hilal Manzur al Falsafi - Muhammad Naufal Annabil (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The aim of this article is to analyze a feminist Arabic literary criticism research from a philosophical perspective, which includes the ontology, epistemology, and axiology of the research. The research subject analyzed was the poem